Environmental regulation and urban position in the inter-urban pollution transfer network: A perspective on network analysis of pollution-intensive enterprises’ relocation - Lu, Chen; Ouyang, Qijuan (Journal of cleaner production, 2024)
Given the unstable global political situation and increasing uncertainty of worldwide trade, governments and enterprises value more on domestic relocation and cooperation which could lead to a tendency of more pollution transfer within a country. Previous studies have revealed the impact of environmental regulation on enterprises' relocation, but the relationship between urban environmental regulation and its position in the inter-urban pollution transfer network has not been revealed. This paper studies how environmental regulations imposed by local governments have influenced the inter-urban pollution transfer network within a country. Based on theoretical analysis, we apply the econometric models to a unique dataset on firm-level relocation activities of listing polluting enterprises in China from 2010 through 2019. We find that the inter-urban pollution transfer network with hierarchical structures evolves rapidly, and there is increasing nationwide pollution transfer between cities in China. Environmental regulation positively affects urban net out-degree centrality in the pollution transfer network by increasing polluting enterprises’ compliance costs. There is a spillover effect of environmental regulations, and environmental regulations in neighboring cities impact more on local net out-degree centrality in the pollution transfer network. •The inter-urban pollution transfer network has hierarchical structures.•Environmental regulation positively affects urban position in the network.•Environmental regulations have spillover effects on urban position in the network.•Polluting enterprises' relocation is driven by compliance costs.